Uji MPN Coliform pada Air Isi Ulang dengan Sterilisasi Sinar UV - Widodo; Dian Yulia Purwanti; S.Y Didik Widiyanto; Devi Etevia Purlinda (Jaringan Laboratorium Medis, 2026)
Wolter Refill water typically undergoes a filtration and sterilization process using 254 nm UV light to sterilize against microbial contamination. This bacterial contamination can be tested using the MPN Coliform test, which is the most important microbiological parameter for drinking water quality. Fecal coliform bacteria are the most commonly used microorganisms as indicators of water pollution, as these bacteria are always present in feces. According to Indonesian Minister of Health Regulation No. 492/MENKES/PER/IV/2010, mandatory standards for drinking water quality are regulated, including physical and microbiological requirements. The purpose of this study was to identify the presence of coliform and fecal coliform bacteria in AMIU sold along Jalan Wolter Monginsidi, Semarang, and to analyze their presence in drinking water. The research method was descriptive. The object of the study was AMIU from eight AMIU depots sold along Jalan Wolter Monginsidi, Semarang, while the subjects were coliform and fecal coliform bacteria. The data collected consists of primary data and supporting data which are then arranged descriptively. Research results There are 3 AMIU depots that are positive for containing Coliform bacteria, namely Depot A4, A5 and Depot A8 with a total Coliform bacteria content of 2 MPN / 100 ml. While the 8 AMIU depots studied did not contain fecal Coliform bacteria, namely 0 MPN / 100 ml. The causes of the presence of Coliform bacteria in positive AMIU samples include the sterilization method only using UV light, the sterilization time is less than 1 hour, the sterilization tool is not replaced periodically, the AMIU storage time at the depot is more than 3 days, the gallon is not washed properly, and the AMIU Laboratory is not checked routinely. Poor results in the test are submitted to the depot manager for follow-up by resetting the sterilization tool.